PENGARUH EKSPOR DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI - Fitra Annisa; Mutiara Arlina Rahmadani; Dio Kurniawan; Marina Marina; Bukhari Muslim; Jolianis Jolianis (STKIP Persada Khatulistiwa Sintang, 2026)
The purpose of this study is to determine and analyze the influence of exports and investment on Indonesia's economic growth, both partially and simultaneously. Data collection techniques used documentation, with data sources obtained from BPS (Central Statistics Agency) Indonesia and the World Bank for the period 1960-2024. Data analysis was conducted using the multiple regression method. The results of the study indicate that exports and investment do not have a significant influence on economic growth, either partially or simultaneously. This indicates that the level of exports and investment does not affect economic growth. One of the causes is unequal economic growth due to disparities between urban and rural areas, as well as between western and eastern Indonesia. This finding indicates that these variables are influenced by other, more dominant factors, so they do not have a strong enough impact on national economic growth. This study suggests the need for more in-depth studies of other variables that can influence economic growth and the importance of more focused policies to increase the contribution of exports and investment. Other factors include: infrastructure, macroeconomic conditions (inflation, interest rates), economic diversification, innovation and technology. This research has time limitations, because it does not cover long-term economic boundaries and the limited variables measured do not include macroeconomic variables as factors that influence economic growth.